Incentive Contracts, Market Risk, and Cost of Capital - Bertomeu, Jeremy (Contemporary Accounting Research, 2015)
Abstract Should incentive contracts expose the agent to market‐wide shocks? Counterintuitively, I show that market risk cannot be filtered out from the compensation and managed independently by the agent. Under plausible risk preferences, the principal should offer a contract in which performance pay increases following a favorable market shock. In the aggregate, however, the effect of market risk on individual contracts diversifies away and the agency problem does not directly affect the cost of capital. The analysis suggests caution in interpreting changes in cost of capital in terms of the stewardship role of accounting information.